2011
DOI: 10.1007/s00264-011-1420-6
|View full text |Cite
|
Sign up to set email alerts
|

The primary stability of angle-stable versus conventional locked intramedullary nails

Abstract: Purpose The aim of this study was to compare the initial biomechanical characteristics of the angle-stable locking system for intramedullary nails using the new biodegradable sleeve with conventional locking in the treatment of unstable distal tibial fractures. Methods Eight pairs of fresh, frozen porcine tibiae were used for this study. The expert tibial nail (Synthes) was equipped with either conventional locking screws (CL) or the angle-stable locking system (AS). This system consists of a special ASLS scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 27 publications
1
12
0
3
Order By: Relevance
“…In a former study our group already investigated the primary biomechanical fixation stability of the new biodegradable sleeve. In this study we found the angle-stable locked constructs providing a significantly higher torsional and axial primary stability compared to conventional locking [17]. In the present study we could affirm the advantage of the angle-stable locking especially for torsional fixation stability over a time of 12 weeks.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In a former study our group already investigated the primary biomechanical fixation stability of the new biodegradable sleeve. In this study we found the angle-stable locked constructs providing a significantly higher torsional and axial primary stability compared to conventional locking [17]. In the present study we could affirm the advantage of the angle-stable locking especially for torsional fixation stability over a time of 12 weeks.…”
Section: Discussionsupporting
confidence: 72%
“…First using a PEEK (polyetheretherketone) sleeve, the manufacturer completely changed the sleeve material to biodegradable 70:30 poly(L-lactide-co-D,L-lactide). In a previous study our group could already show the significant increase of initial torsional stability due to angle-stable locking [17]. …”
Section: Introductionmentioning
confidence: 99%
“…When using ASLS, the sleeve might create a superior condition of continuous load transfer and may act as an additional shock absorber truncating force peaks. Angle stable locking diminishes screw toggling as indicated by increased construct stiffness, which contributes to interfragmentary stability at the fracture site [21].…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have demonstrated the advantages for the angular-stable locked nails with regard to a significantly higher axial and torsional stiffness, significantly less fracture gap movement and a significant reduction of the neutral zone in bending [6][7][8][9]. Biomechanically, two ASLS locking screws provide equal stability to three standard locking screws [10].…”
Section: Introductionmentioning
confidence: 99%